2013
DOI: 10.1007/s10548-013-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Correlates of Processing Own- and Other-Race Faces

Abstract: Most adults have more experience in identifying faces of their own race than in identifying faces from another race, and thus may be considered as own-race face experts. This effect was investigated by recording and analyzing ERPs as well as induced gamma oscillations. The race modulation occurred post the stage of structural processing revealed by N170. Larger P2 component and induced gamma activity for own-race than other-race faces could be associated with more elaborate processing on the basis of configura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 64 publications
8
26
0
Order By: Relevance
“…The N170 inversion effect has been suggested to reflect perceptual expertise for a given class of stimuli (Rossion et al, 2002), and larger effects for own-race faces are therefore well in line with expertise accounts of the own-race bias (e.g., Tanaka et al, 2004; Rossion and Michel, 2011). The present finding is also in line with those previous studies that observed a larger N170 FIE for own-race faces (Vizioli et al, 2010a; Caharel et al, 2011), but not with others that did not (Wiese et al, 2009; Chen et al, 2013). While the reason for this discrepancy remains somewhat unclear, it may be related to the fact that Chen et al (2013) tested exclusively Chinese participants.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The N170 inversion effect has been suggested to reflect perceptual expertise for a given class of stimuli (Rossion et al, 2002), and larger effects for own-race faces are therefore well in line with expertise accounts of the own-race bias (e.g., Tanaka et al, 2004; Rossion and Michel, 2011). The present finding is also in line with those previous studies that observed a larger N170 FIE for own-race faces (Vizioli et al, 2010a; Caharel et al, 2011), but not with others that did not (Wiese et al, 2009; Chen et al, 2013). While the reason for this discrepancy remains somewhat unclear, it may be related to the fact that Chen et al (2013) tested exclusively Chinese participants.…”
Section: Discussionsupporting
confidence: 94%
“…The present finding is also in line with those previous studies that observed a larger N170 FIE for own-race faces (Vizioli et al, 2010a; Caharel et al, 2011), but not with others that did not (Wiese et al, 2009; Chen et al, 2013). While the reason for this discrepancy remains somewhat unclear, it may be related to the fact that Chen et al (2013) tested exclusively Chinese participants. Recent evidence suggests that Asian participants show a similar degree of holistic processing for own- and other-race faces (Crookes et al, 2013), possibly reflecting a larger degree of variability tolerated by the face processing system of this participant group.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations